2001
DOI: 10.1177/1356336x010072003
|View full text |Cite
|
Sign up to set email alerts
|

Dance Movement Therapy in the UK: A Field Emerging from Dance Education

Abstract: Dance Movement Therapy (DMT) in the UK is derived from dance education, as well as other associated fields. Although DMT is growing in terms of numbers of practitioners and client populations, only very limited information is available concerning the theoretical bases and principles underlying the practice of DMT, as well as the backgrounds of therapists. A nationwide study was therefore undertaken at the University of Manchester, UK (1994-8), which aimed at describing the field of DMT, as well as other Arts T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The presence of a therapeutic relationship is a key difference between dance as a sensitive form of teaching or community practice on the one hand and DMT as a form of psychotherapy on the other (Karkou and Sanderson, 2000, 2001, 2006; Meekums, 2002). This relationship is also highly valued as an agent of change for clients with depression who often experience isolation and loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a therapeutic relationship is a key difference between dance as a sensitive form of teaching or community practice on the one hand and DMT as a form of psychotherapy on the other (Karkou and Sanderson, 2000, 2001, 2006; Meekums, 2002). This relationship is also highly valued as an agent of change for clients with depression who often experience isolation and loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…While they did not include comparison groups, they demonstrate the importance of considering the relationship between interaction partners over time when examining SMS in autism. Approaches such as Dance and Movement Therapy place central importance on the developing relationship between the therapist and the client ( Karkou & Sanderson, 2001 ). All six papers demonstrated close SMS between autistic children and their partners in therapeutic interactions and found an increase over time for pairs that remained consistent ( Dvir et al, 2020 ; Griffioen et al, 2020 ; Koehne et al, 2016 ; Manders et al, 2021 ; Venuti et al, 2017 ; Yoo & Kim, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mental stress associated with abject poverty (Department of Education, 2002), crime, domestic violence, child abuse, dysfunctional families (van Niekerk, 2008), and the rapid spread of HIV and AIDS (Wood, 2009) confront South African citizens on a daily basis. The responses indicated that dance education not only provided the participants with a channel for tension release, it also provided a mental space where they could escape the stark realities of everyday life, confirming dance's therapeutic value (Karkou & Sanderson, 2001). …”
Section: Liberating the Selfmentioning
confidence: 99%